Sosialisasi dan Pelatihan Pembuatan Produk Pangan Berbasis Limbah Buah-Buahan di Desa Aik Bukak, Kecamatan Batukliang Utara, Lombok Tengah - Sukenti, Kurniasih; Julisaniah, Nur Indah; Sukiman, Sukiman; Aryanti, Evy; Mulyaningsih, Tri; Nurrijawati, Nurrijawati; Permatasari, Baiq Dewi; Faroby, Muhammad Azdy (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2025)
Aik Bukak Village, North Batukliang District, Central Lombok is an agricultural area with the majority of its people making a living as farmers, apart from managing their yards by growing vegetables and fruit. Several types of fruit are found in quite large quantities and are available almost all year round, whether they come from the garden or not, for example bananas, watermelon and durian. At certain times fruit is available in large quantities, and accompanied by large amounts of waste which is often not utilized, other than as raw material for making organic fertilizer. Basically, this type of waste can be processed into food or snacks, which apart from being useful as an alternative food ingredient, as an effort to diversify food, is also an alternative to increase household income. The aim of this activity is to provide outreach and training in making food products based on local fruit waste in the Aik Bukak Village community. The method used is to conduct lectures, discussions and demonstrations of fruit waste processing by involving the community. From the results of the activity, it can be concluded that the community has additional knowledge regarding the use of fruit waste as food, in the form of banana peel chips, candied watermelon peels, and jackfruit seed cakes. Apart from reducing the potential for environmental pollution, people also have alternative businesses to increase household income.